2005
DOI: 10.1007/s10439-005-2499-y
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Fluid Mechanical Disturbance Induced by Endovascular Stents

Abstract: Arterial restenosis following stent deployment may be influenced by the local flow environment within and around the stent. We have used computational fluid dynamics to investigate the flow field in the vicinity of model stents positioned within straight and curved vessels. Our simulations have revealed the presence of flow separation and recirculation immediately downstream of stents. In steady flow within straight vessels, the extent of flow disturbance downstream of the stent increases with both Reynolds nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 40 publications
3
116
0
Order By: Relevance
“…Previously, it has been shown that local flow disturbances caused by stent struts result in low wall shear stress and re-circulating flows [22][23][24]. Local flow disturbances induced by stents eventually return to normal flows with large stent strut spacing corresponding to more rapid flow restoration [23].…”
Section: Effects Of Stent Strut Placement On Perforator Flowsmentioning
confidence: 99%
“…Previously, it has been shown that local flow disturbances caused by stent struts result in low wall shear stress and re-circulating flows [22][23][24]. Local flow disturbances induced by stents eventually return to normal flows with large stent strut spacing corresponding to more rapid flow restoration [23].…”
Section: Effects Of Stent Strut Placement On Perforator Flowsmentioning
confidence: 99%
“…These computational methods of analysis employ sophisticated numerical techniques, such as the finite element and finite volume methods, to obtain approximate numerical solutions to complex physical problems. To date, a large number of studies have carried out computational structural (CS) analyses 1,4,5,14,15,19,[25][26][27][28][29]37,44,53,54,57,59,[62][63][64]72,73,78,80,85,87,[90][91][92] and computational fluid dynamics (CFD) analyses 3,8,9,12,30,31,33,42,[47][48][49][50][51]65,66,69,[74][75][76]83,89 ...…”
Section: Introductionmentioning
confidence: 99%
“…Although nonNewtonian behavior can be expected if the shear rate is less than 100 s −1 (Seo et al 25 ) this effect is not considered here; furthermore, the framework of this study is based on the work done by Charonko et al 13,14 in which the working fluid was a mixture of water and glycerine approximating the density and viscosity of human blood. Gravity is neglected in this problem as it has minor effect in comparison with pressure and viscous forces.…”
Section: Problem Formulationmentioning
confidence: 99%